Influencia de la depresión en la calidad de vida de los adultos mayores del Recinto Sabanetillas del cantón Echeandia de la Provincia de Bolívar - Posligua Marcllo, Diana Carolina (2023)
The present research seeks identifies the influence of Depression on the quality of life in older adults in the Sabanetillas Campus of the Echeandía Canton of the province of Bolívar, because from the age of 65 years onwards, there are multiple changes at a physical level, psychological, social, work and includes the spiritual. The beneficiaries of the research are 62 older adults from 65 years of age and older. In addition, relevant, reliable data from a situational diagnosis are revealed, which will subsequently serve to create action plans, provide comprehensive assistance and in turn as a source of information for future research. The methodology applied is with a mixed approach, that is, qualitative and quantitative, with a non-experimental design, with a cross-sectional design, techniques and instruments are applied through the collection of information such as observation, structured interviews, instruments such as Adaptation of the Social assessment form of the Ministry of Economic and Social Inclusion, the Yesavage Depression Scale shows that 10 older adults have 16% mild depression, 36 with 58% moderate depression, 16 with 26% severe depression, the WHOQOL-BREF Scale found in 33 older adults, that is, 53% suffer from poor quality of life, 29 suffer from 47% average quality of life, which is related to the domains with 81% affectation in physical health, 87% in psychological health, 77% difficulty in social relationships and 90% according to the environment, which allow us to conclude that depression influences the quality of life of older adults in the aforementioned population.